The home care reablement study: A mixed methods study - Bennett, Cate (2024)
I. Abstract Background In England in 2021/22, there were 818,000 people who received funded long-term social care support, primarily in residential, nursing homes, or in their own homes. In addition, there were 224,000 episodes of short-term care provided. Reablement is a short-term service mostly provided in the person’s home to help them become independent in activities of daily living and reduce dependency. Traditionally, home carers are trained to ‘do things’ for people, whereas reablement services aim to get people to engage in activities for themselves. ACT reablement is a programme especially developed by social care occupational therapists to train independent sector home carers to deliver reablement. ACT (adult care training) involves training reablement competency through action learning sets, ongoing reflective case work discussion, and proactive, responsive occupational therapy solutions. The underpinning philosophical positions developed in this thesis were aligned to the critical realism philosophical perspective, strength-based approach, positive psychology theory and occupational science. The aim of the studies in this thesis were to define reablement, investigate reablement outcomes, understand home carers’ experiences of reablement, to define ACT, evaluate and refine its delivery and to provide recommendations for future research. Ethical approval was given by the Nottingham University Research Ethics Committee reference FMHS-261-0521. Methods A scoping literature review was completed to explore and define reablement. A systematic literature review of randomised controlled trials (RCTs) was completed to determine the effectiveness of reablement. A before and after study of ACT was completed. The ACT training was defined and refined using the literature review findings, and training resources were co-designed by an expert group. Home carers were recruited from one home-based care provider. Data was collected from 22 home carers using a before and after training survey, with missing data for 1 participant. Post-training interviews, and focus groups, were completed with a subset of 14 participants. Survey data was analysed using descriptive statistics and results presented as median average with interquartile range, and proportion of grouped positive or negative responses. The transcribed semi-structured interview and focus group data were coded using a two-step coding method and thematically analysed using Framework Analysis. The survey, interview and focus group data was synthesised using a mixed methods convergent design. This enabled a collaborative cycle of improvement to refine the ACT programme. Results The scoping review sourced 42 studies from 11 countries spread over 10 years. The results highlighted that reablement interventions varied in content, aim, duration, and service delivery model. Few studies reported on whether reablement interventions changed people’s behaviour or outcomes, worker training, staff competencies, or professional support. The systematic review found eight RCTs, with 1,777 participants, from six countries between 2012 – 2021 with diversity in interventions. Outcome measures featured change in home care hours, functional ability, mobility, and quality of life. Studies with an occupational therapist involvement showed greater, but non-statistical, improvement in outcomes. The pre-and post training survey was completed by 21 (95.5%) home carers, 19 (86.5%) were female with an average age between 35-44 years; 19 (86.5%) identified as belonging to white ethnicity, and 2 (9%) as belonging to a black, asian or minority ethnic group; 13 (59%) had more than 11 years experience as a home carer. Before training, 9 (41%) of the home carers were clear about the difference between reablement and standard home care. Whereas after, this increased to 21 (95.5%). Before training, 6 (28%) found it difficult to engage people in reablement goal attainment conversations, after training 21 (95.5%) indicated they were happy about having these conversations. Before training, 10 (45%) found motivating people difficult, and after training 21 (95.5%) said they had no difficulty in motivating people. Before training, 11 (50%) were confident identifying improvements in people and after training this had risen to 21 (95.5%). Finally, before training, 16 (73%) were confident feeding back to the occupational therapist and after training 21 (95.5%) were confident. After the training, 14 (63%) of the home carers participated in interviews two months later, or attended focus groups the same day. Two themes emerged. 1. The home carers experience of reablement – the home carer`s believed that people associated home care with having things done for them, including housework. They frequently found family expectations were challenging when relatives had a different mindset or opinion. They felt this led to dissatisfaction, power imbalance and conflict for home carers and the people. They found it difficult to recognise a person’s capability for improvement or judge whether people could progress due to being sent to different people each day. They were perplexed when the person had achieved a level of independence and then the care package was not reduced. Some home carer`s felt that the time needed to deliver reablement was justified, whereas others felt it was better to help the person and have a shorter visit. 2. Knowledge and skills – some of the home carer`s were confident and positively articulated their knowledge and use of reablement, whereas others were uncomfortable about doing this. Most were able to describe the key elements of reablement and were happy to take responsibility for managing risk and make autonomous decisions. A few home carer`s expressed dissatisfaction that reablement was designed to only reduce costs and not improve lives. Contrasting views and attitudes emerged about doing things for people. There was a lack of understanding from most of the home carer`s about the use of equipment. The interview and focus group findings confirmed that ACT training was acceptable, had fidelity and was feasible to deliver in other settings. The home carer`s preferred an interactive face-to-face, discussion-based learning style. As a result, ACT was refined to one five-hour, face-to-face session incorporating action learning sets, strength-based competency training, goal setting, activity analysis, pacing activities and reflective case discussions with an occupational therapist. Conclusions Reablement is a complex intervention, poorly defined and delivered by a range of health and social care workers. Training is variable and rarely evaluated. These findings are in line with other research studies. This study provides evidence that ACT can be delivered and is acceptable to independent sector home care workers. It has been proven to positively change the mindset of home carers, but we do not know if this influenced their behaviour long-term, and whether this has an impact on the well-being of the person who needs care. Home carers are ready to be involved in research this is one of very few studies that has heard their voice. More research is needed with this under served community. Relevance to patients/public, other scientists Independent sector home carers need to be trained to deliver reablement. By defining the ACT programme, and determining it`s feasibility and fidelity it is possible to evaluate it further for delivery to other home care providers.